Poorly cohesive duodenal carcinoma mixed with signet ring cell carcinoma with systemic metastasis: a case report and literature review - Tang, Song; Li, Xinjun; Wu, Aiguo (Frontiers in Oncology, 2023)
Duodenal poorly cohesive carcinoma mixed with signet ring cell carcinoma is very rare and no cases have been reported. When it occurs distant metastasis, it is very easy to be misdiagnosed. We report the first case of a 52-year-old male patient with poorly cohesive carcinoma of the duodenum mixed with signet ring cell carcinoma with systemic metastasis. The process of its diagnosis and differential diagnosis is highlighted.